Evaluation of individual stock portfolio performance on the Indonesia stock exchange using the Ortiz, Jorion, and Markowitz approaches - Enggal Dwi Mulyaningtyas; Rofikoh Rokhim (Economic Military and Geographically Business Review, 2026)
Background: Indonesia's capital market has experienced a sustained increase in investor participation, creating a stronger need for systematic and implementable portfolio construction methods. This study evaluates estimation risk in mean-variance optimization by comparing traditional Markowitz optimization with two mean-shrinkage approaches: the parameter-focused Bayes-Stein estimator of Jorion and the decision-focused optimal shrinkage of means proposed by Ortiz et al. Methods: The study uses monthly individual stock data from the Indonesia Stock Exchange over January 2006-December 2025. Excess returns are calculated relative to a monthly risk-free proxy, and portfolios are evaluated using a 120-month rolling-window out-of-sample backtest under long-only constraints. The sample is a balanced panel of 74 stocks with complete monthly data, and the monthly deposit insurance rate of the Indonesia Deposit Insurance Corporation (LPS) is used as the risk-free proxy. Portfolio performance is assessed using monthly and annualized Sharpe ratios, while weight stability is assessed using average weight volatility and turnover. Newey-West tests are used to evaluate whether differences across methods are statistically significant. Findings: The Ortiz approach consistently selects an optimal shrinkage intensity of zero, making its weights and performance effectively identical to the traditional Markowitz portfolio. Markowitz and Ortiz record an annualized out-of-sample Sharpe ratio of 0.0713, while Jorion records 0.0608. The statistical tests indicate that differences in out-of-sample performance and stability are not significant across the three approaches. In economic terms, the annualized Sharpe ratios of all three methods are very low (below 0.08), indicating that long-only optimization of individual Indonesian stocks delivered only marginal risk-adjusted excess returns over the sample period. Conclusion: In the Indonesian stock market setting, more complex mean-shrinkage methods do not automatically produce superior portfolio outcomes. Novelty/Originality of this article: This article provides Indonesian market evidence on the comparison between parameter-focused and decision-focused shrinkage approaches within a consistent rolling-window portfolio backtesting framework.